A joint photoacoustic imaging and broadband spectral analysis for early-stage intraoperative pathology assessment: A case study with colorectal cancer - Fan Yang; Zhengduo Yang; Zheng Zhu; Siwei Zhu; Wei Song; Yong Yang; Xiaocong Yuan (Photoacoustics)
Accurate and rapid intraoperative diagnosis of micro-infiltration in early-stage tumors presents a formidable challenge for decades. Here, we propose a novel diagnostic approach, that combines Photoacoustic Morphological Imaging (PAMI) with an in situ broadband Photoacoustic Spectral Analysis (PASA), to implement intraoperative assessment of early-stage tumor while its high-frequencies between 50 and 150 MHz respond to various nuclei specifically. Our system, a broadband Ultraviolet Photoacoustic Microscopy (bUV-PAM), uniquely integrates ultraviolet laser-induced nucleus-specific photoacoustic excitation with broadband photoacoustic detection (up to 176 MHz at −6 dB) via an optical surface wave sensor. This approach facilitates the simultaneous acquisition of morphological and spectral information from unstained tissue sections, yielding a comprehensive dual-modality virtual slice within a single raster scan. Using human colorectal tissue samples, we applied the joint PAMI and in situ PASA approach across 6 case groups. Morphological features in PAMI showed a high concordance with Hematoxylin and Eosin (H&E) staining, whereas micro-infiltrative features were too indistinct to be identified in both PAMI and H&E images. In contrast, the PASA effectively distinguishes between micro-infiltrated and non-infiltrated tissues, a finding validated by subsequent Immunohistochemical (IHC) assessments. The preliminary results suggest that the joint approach holds potential to enhance intraoperative detection of micro-infiltration, thereby offering a promising avenue for accurate and rapid surgical margin assessment.